Carcass growth and properties in Colombian Criollo Hair Sheep (OPC) and F1 Dorper x OPC: Características de crecimiento y de la canal en ovinos criollos y F1 Dorper - Vergara-Garay, Oscar (2023)
The aim of this study was to evaluate the productive performance and carcass characteristics in Creole hair sheep (OPC) and F1 Dorper x OPC crosses in Córdoba, Colombia. Twenty-five lambs (14 F1 Dorper x OPC and 11 OPC) were used (9 males and 16 females), managed in a semi-stall system and supplemented with a mixture of cottonseed and ground corn. The lambs were slaughtered at approximately 6.5 months of age. The effect of sex, type of parturition (single, twins) and breed type was determined. Within the productive performance, only a significant difference was found in the pre-weaning weight gain (p<0.05) due to sex and breed type. Carcass characteristics were significant for the breed type effect, rump width/leg length ratio, leg and rump girth, rump, hip and leg width, loin eye area, and width and depth of the back. It is concluded that the F1 animals presented better performance than the OPC for growth and carcass characteristics.